Monetary and Fiscal Management, Finance, and Growth - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2004)
This lecture addresses three related aspects of monetary and fiscal management in Europe and elsewhere. First, I discuss the implications of economic integration for monetary and fiscal policy, especially the narrow focus on low inflation as the main objective of monetary policy. I argue that because inflation springs from several sources, monetary authorities held responsible by law for maintaining low inflation need to exercise their newfound independence by reserving the right to address all sources of inflation. In this context, I also ponder the question whether increased independence of fiscal policy from short-term political interference would be desirable. Second, I present new empirical evidence of the relationship between inflation, finance, and economic growth across countries, arguing that long-run growth considerations provide an important additional justification for why price stability ought to remain a priority of independent policy makers. Third, I review some further aspects of the relationship between fiscal policy and economic growth, emphasizing the traditional three-pronged role of fiscal management: stabilization, allocation, and distribution, all of which can be conducive to growth. The argument leads to the conclusion that only the stabilization function of fiscal policy and perhaps also some aspects of the allocation function could be usefully delegated in an attempt to immunize them from shortsighted and socially counter-productive political interference, but not the distribution function.
Keywords: 330